Pengaruh Financial Literacy dan Financial Managament Behavior Terhadap Invesment Decision pada Investor Generasi Y dan Z di Kota Bogor - Sophie Indah Rahayu (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This research aims to determine the influence of financial literacy variables and financial management behavior on investment decision variables among Generation Y and Z investors in Bogor City. The population in this research is the people of Bogor City with a sample size of 100 respondents (investors) using the Slovin formula which has criteria for respondents using a purposive sampling technique. The method in this research is quantitative using questionnaire data collection techniques with multiple linear regression analysis techniques. Based on the research results, it shows that partially financial literacy has a significant positive effect on investment decisions, financial management behavior has a significant positive effect on investment decisions and simultaneously financial literacy and financial management behavior have a significant positive effect on investment decisions